Non-invasive positive pressure ventilation offers greater improvement in COPD-related respiratory failure when combined with naloxone (Bangladesh Journal of Pharmacology, 2016)
To improve efficacy of non-invasive positive pressure ventilation (NPPV), this study investigated the combination of NPPV with naloxone in COPD patients with respiratory failure. One hundred four patients with COPD-related respiratory failure were enrolled prospectively and randomly divided into a control group treated with NPPV alone (n = 52) and an observation group treated with NPPV combined with 4.0 mg naloxone by continuous infusion (n = 52). At 3 and 5 days after the start of treatment, the respiratory mechanics, pulmonary function, and oxygen metabolism parameters were significantly improved in the NPPV + naloxone group compared to the NPPV alone group (p